Silk fibroin-based polymeric membranes for fuel cells - Almeida, Tomás Coelho (2020)
Polymer electrolyte fuel cells (PEFCs) have been widely used for their ability to generate electricity in a sustainable way. However, the materials used in PEFCs present themselves with clear negative environmental impacts. Thus, the search for alternative materials is a critical aspect in order to improve the sustainability of such technologies. This dissertation aimed at the development of polymeric membranes of silk fibroin, a protein produced by the domestic silkworm, not thoroughly explored for fuel cell related applications. In an initial phase of this work, two methods for fibroin extraction and purification were tested and the one that proved to be more reproductive was chosen. After that, the membrane preparation conditions were studied and optimized, using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and scanning electron microscopy (SEM), and a significant impact on the structure of fibroin by the evaporation process of water was verified. Considering the application in PEFCs, the ion-exchange capacity (IEC), dynamic water vapor sorption (DVS), thermal and mechanical properties were also studied. The obtained results demonstrated that when the -sheet fraction is higher in the membrane structure, water sorption is up to 28% of its mass, at 25 °C. Finally, the ionic conductivity of the membranes was evaluated by impedance spectroscopy, at different temperature (T) and relative humidity (RH) conditions. Silk fibroin membranes present ionic conductivity values ranging from 5.7 107 S.cm1, at lower temperatures and relative humidities, to 1.8 103 S.cm1 at RH = 98% and T = 94°C. The obtained values for conductivity are lower when compared with commercial membranes based on Nafion®, however, the silk fibroin membranes still demonstrate promising results regarding thermal and mechanical properties, with degradation temperatures up to 260 °C. As a biopolymer with such promising properties, silk fibroin is a material with potential application in PEFCs